Show Back: Developing and Testing of a Simulation-Based Assessment Method for Identifying Problems in Self-Management of Medications in Older Adults. Issue 3 (September 2018) - Kapoor, Alok; Burns, Laura; Foust, Janice B.; Sarno, Maureen; Callahan-Lydon, Jeanne; Schultz, Paula; Donovan, Jennifer; Kanaan, Abir; Crawford, Sybil; Gurwitz, Jerry H.; Mazor, Kathleen M.
Abstract : Supplemental digital content is available in the text.